Genetic diversity of the Macaronesian leafy liverwort Porella canariensis inferred from RAPD markers - Spínola, Hélder (2017)
Plant colonization of the North Atlantic raises the intriguing question of the relationships between extant island species with their continental counterparts (European, African, and American), which may provide clues to past geographic distribution and colonization history. It has been suggested that during past glaciations, many plant species with typical Mediterranean distributions survived in the Atlantic islands that belong to what is today known as Macronesia. We used random ampliﬁed polymorphic DNA (RAPD) markers to study 12 populations of the liverwort Porella canariensis partly covering its present-day distribution (Azores, Madeira, Canary and Cape Verde Islands, and Iberian Peninsula). Unweighted pairgroup (UPGMA) and principal component (PCO) analyses showed a similar geographical pattern that suggested a close relationship between Iberian populations and those from the Canaries and Cape Verde Islands. Populations from Madeira had more genetic variation than those from the Azores, a result from either a richer diversity of habitats in Madeira, which prompted more population diversiﬁcation, successive colonization waves from different origins, or an older colonization of Madeira. The data show that continuous patches of liverworts are often comprised of more than one individual. Finally, RAPDs can be used to investigate intraspeciﬁc diversity within a comparatively large geographic area and, with utmost care, can be used to infer a historic context to explain the patterns observed.